FINANCIAL SUPPORT AND COMPETITIVE ADVANTAGE OF SELECTED FINANCIAL TECHNOLOGY FIRMS IN LAGOS STATE, NIGERIA - Ayodeji Gbenga Bamidele; Edafe Bawa Dogo (Malete Journal of Accounting and Finance, 2024)
The competitive landscape of financial technology (fintech) industry in Nigerian is challenged by several factors such as underserved consumer needs, as well as funding shrinkage occasioned by global investment decline. This recoil necessitates a deep understanding of the factors that affects their competitive advantage. This study thus investigates the impact of financial support, a business incubation strategy on competitive advantage of fintech firms in Lagos State, Nigeria. This study adopts a survey research design to collect primary data from a population of 200 owners/managers of registered fintech firms in Lagos State, Nigeria. Total enumeration was used to determine the sample size of 200 owner/managers. Data was collected using an adapted and close ended questionnaire and a response rate of 73% (146) was obtained. The validity and reliability of the research instrument was established using Average Variance Extracted, Composite Reliability, and Cronbach’s alpha coefficients, thus ensuring its accuracy and consistency. Descriptive statistics and inferential statistics were utilised to analyse the data. The findings of the study revealed that financial support does not exhibit a significant effect on competitive advantage (β = 0.067, R2= 0.028, p > 0.05) fintech firms in Lagos State, Nigeria. Based on the conducted investigation, it is clear that the impact of financial support alone on competitive advantage in fintech enterprises may not be statistically significant. The study therefore recommends that fintech companies in Lagos State, Nigeria should pay attention to other factors not limited to financial support, to help meet the growing consumer needs and build their competitive advantage